Vibration-assisted forward osmosis process for mitigation of concentration polarization in submerged hollow fiber membrane system - Low, Kay Siang (Nanyang Technological University, 2020)
Concentration polarization results in significant reduction in the difference in osmotic pressure between the draw solution and the feed solution in forward osmosis (FO) and is regarded as a major challenge in the FO process. Hence, mitigating concentration polarization is essential for increasing the efficiency of the FO process. In the current study, vibration of hollow fiber (HF) membranes was systematically studied as a method for the mitigation of concentration polarization in submerged FO process. A membrane module consisting of polyether sulfone (PES) HF membranes with inner selective layer was designed and fabricated. Using a water flux model that takes into account the internal concentration polarization (ICP) and external concentration polarization (ECP) on both the lumen and shell sides of the HF membranes, the vibrating frequency and amplitude were evaluated with regards to the change of mass transfer coefficient. Results showed that when low vibration frequency and amplitude of (3 Hz and 1.2 cm) were applied, the mass transfer coefficient increases from 0.7×10-5 m/s (at no vibration) to 1.8×10-5 m/s, which approaches the optimal value as determined from the FO modelling results. The effects of the vibration of membranes were then evaluated in the active layer facing feed solution (AL-FS) and active layer facing draw solution (AL-DS) orientations. Results showed that in the AL-FS orientation, vibration could enhance mass transfer coefficient significantly at low water flux. However, in the AL-DS orientation, the enhancement of mass transfer coefficient was minimal at low water flux level due to minimal concentrative ECP present. Interestingly, there was significant improvement of mass transfer coefficient at high DS concentration/high water flux level attributed to the significant concentration polarization under high water flux condition. In addition, the vibration-assisted FO process was carried out using polyelectrolyte poly (sodium-4-styrenesulfonate) (PSS) as a draw solute. The change of draw solute to PSS has limited effects on the vibration, as the low diffusion coefficient and high viscosity of PSS offsets the benefits of vibration of membranes. In summary, this study demonstrated a facile method for mitigating concentration polarization in submerged FO process, whereby vibration of HF membranes at low frequency and amplitude could enhance FO water flux by improving hydrodynamic mixing and induce boundary layer disturbances at the shell side of submerged HF membranes. The method could possibly be adopted for improving FO efficiency in submerged osmotic processes.